Diversity and abundance of fish larvae in the Klang Strait in relation to anthropogenic impacts / Cecilia Chu - Cecilia, Chu (2021)
The estuarine area of the Klang Strait, located on the west coast of Peninsular Malaysia, harbours many species of fish inside its mangrove creeks and deltaic islands. The Klang estuary is indeed known as the spawning, nursery, and feeding ground for many coastal fishes with economic or ecological importance. However, only one study has ever been conducted which described the larvae of two species of engraulids that occur in the area. The current study was therefore conducted in an attempt to identify and describe the species of larvae or larval families that occur in the Klang Strait. DNA barcoding method was used to identify larvae by matching of DNA sequences. Of the 250 individual larvae that were selected for molecular identification, 193 DNA sequences were successfully sequenced. A total of 48 putative species were identified, which belonged to 21 families of larval fishes in 7 different orders. Gobiidae was the most diverse family containing at least 13 species. On the other hand, Ambassidae, Clupeidae, and Blenniidae contained only one to two species despite being abundant. Currently, there is a lack of reference sequences for speciose and non-commercial fish families such as Gobiidae, Blenniidae, and Callionymidae. Nevertheless, the DNA barcoding method is a useful tool for routine identification of fish larvae. The other objective of the current study was to determine the changes in larval fish assemblages of the Klang Strait after 28 years of coastal development. Archived larval samples from 1985-1986 and 2013-2014 collections were assessed. A Before-After-Control-Impact (BACI) experimental design was established, which included 13 months of sampling prior to the installation of the Kapar Power Station in 1987, and another eight months of sampling since its operation. Substitution of the bottom-dwelling rare families such as the Triacanthidae and Draconettidae with the families Soleidae, Scorpaenidae, and Opistognathidae was observed between the two sampling periods, but dominant families such as Gobiidae, Clupeidae, Sciaenidae, and Engraulidae remained the most abundant. The total larval abundance significantly increased at control stations after impact, which was mostly attributed to the increased abundance of preflexion stage of Gobiidae, Sciaenidae, Engraulidae, Cynoglossidae, and Callionymidae, as well as the preflexion and yolk-sac stages of unidentified taxa. The shift in larval abundances in the Klang Strait was significantly correlated to increased sea surface temperatures and lower pH levels. In contrast, copepod abundance was an unlikely factor that contribute to the increase or decrease of larval fish abundance in this study. This implies that the broad trophic spectrum of estuarine fishes also extends to their larval stages. Therefore, cascading effect on the feeding and growth of larvae due to a reduction in abundances of large-bodied copepod can now be refuted.